2019
DOI: 10.1021/jacs.8b12026
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Block Copolymer-Guided in Situ Fabrication of Stable and Highly Controlled Luminescent Copper Nanoassemblies

Abstract: Assembling instable ultrasmall nanoparticles (NPs) into uniform nanoarchitectures with excellent stability and controllability in aqueous solution is still challenging. Herein, taking the advantage of controllable size and shape of amphiphilic triblock copolymer template, we report a facile and robust strategy for in situ fabrication of highly luminescent Cu nanoassemblies with uniform morphology and remarkable stability. The dominant number of encapsulated CuNPs in an assembly can be controlled through regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Open Access Article. 218 Moreover, the number of the encapsulated CuNCs inside the core can be controlled by adjusting the block segments of the template. The clusters are assembled into uniform structures and held together through the cross-linking of multidentate thiol ligand.…”
Section: Nanoscale Accepted Manuscriptmentioning
confidence: 99%
“…Open Access Article. 218 Moreover, the number of the encapsulated CuNCs inside the core can be controlled by adjusting the block segments of the template. The clusters are assembled into uniform structures and held together through the cross-linking of multidentate thiol ligand.…”
Section: Nanoscale Accepted Manuscriptmentioning
confidence: 99%
“…It is worth mentioning that this strategy gives us insight into designing high-efficiency luminescent CuNCs. It has been found that many CuNCs have unique AIEE properties (Li et al 2016a;Liu et al 2018b;Zhou et al 2019).…”
Section: Solvent Effectmentioning
confidence: 99%
“…The water‐soluble ultrasmall (core sizes: ≈1.8 nm) luminescent PEGlyed AuNPs with ≈600 and 800 nm emissions ( Figure A), respectively, were synthesized according to our previously reported methods (Synthetic details are also shown in Figures S1 and S2, Supporting Information). [ 16 ] The corresponding fluorescence lifetimes were all microsecond time scale (≈1.0–6.8 µs, Figure S3, Supporting Information), indicating triplet excited state is involved in the emission, [ 17 ] which is favorable for 1 O 2 production due to the enhanced chance of energy transfer between triplet electrons from the AuNPs and adjacent 3 O 2 (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%